Analisis Faktor Akibat Perubahan Desain Yang Mempengaruhi Biaya, Waktu Dan Mutu Pada Proyek Konstruksi (Studi Kasus: Pembangunan Gedung Laboratorium Terpadu Kemaritiman) - Melisa Yunisari; Arfan Usman Sumaga; Arfan Utiarahman (Transbahasa, 2025)
Design changes in construction projects often cause significant impacts on the cost, time and quality of work. This study aims to analyze the factors resulting from design changes that affect the construction project of the Maritime Integrated Laboratory Building, Gorontalo State University. This study uses a quantitative descriptive method with data collection through a questionnaire involving 13 respondents, consisting of contractors, consultants, and technical teams. Data were analyzed using the Relative Importance Index (RII) method to identify factors of design changes and their resolution actions. This study aims to analyze the factors and resolution actions of factors resulting from design changes that affect the cost, time and quality of the construction project of the Maritime Integrated Laboratory Building, Gorontalo State University. The results of the study indicate that project delays, daily target inconsistencies, and suboptimal work methods are the main factors that impact costs and quality. Proposed mitigation efforts include better risk management, improved communication between parties, and resource adjustments to minimize negative impacts. This study is expected to contribute to the management of construction projects, especially related to design change management.